Phytochemical and Biological Evaluation on Leaf and Rhizome Extracts of Curcuma caesia Growing in Nepal - Sharma, Tinky; Magar, Akash Budha; Khatri, Sabina; Lohani, Ismita; Pakka, Sangita; Sharma, Khaga Raj (Journal of Nepal Chemical Society, 2025)
Curcuma caesia (Black Turmeric) is a perennial medicinal herb native to Southeast Asian countries of India and Nepal. It is known for its rich phytochemical profile and therapeutic properties. This study investigated the phytoconstituents, biological activities, and toxicity, and performed GC-MS analysis of rhizome and leaf extracts and fractions of C. caesia. Total phenolic content and total flavonoid content were quantified using the Folin-Ciocalteu reagent and AlCl3 colorimetric methods, respectively. The ethyl acetate fraction of the leaf exhibited the highest TPC (91.14 ± 1.55 mg GAE/g), while the aqueous fraction of the rhizome recorded the highest TFC (155.62 ± 0.61 mg QE/g). The ethyl acetate fraction of the rhizome showed the most potent antioxidant activity (IC50 7.58 ± 0.41 µg/mL), and the methanol extract of the leaf showed the highest antidiabetic potential (IC50: 296.69 ± 0.48 µg/mL). Antibacterial activity was observed against Klebsiella pneumoniae, Bacillus subtilis, and Staphylococcus aureus. Toxicity assessment revealed an LC50 of 458.58 ± 20.23 µg/mL for the ethyl acetate fraction of the leaf in the brine shrimp lethality assay. GC-MS analysis identified 9,17-octadecadienal, wilfortrine, and phytol as major compounds. These findings highlight the pharmacological potential of C. caesia and its application in traditional medicine for managing ailments such as stomach aches, migraines, and wounds. Further research is recommended to elucidate its mechanisms of action and develop novel therapeutic agents.